The catalytic role of aspartate in the active site of glutamate dehydrogenase. - Dean, J; Wang, X; Teller, J; Waugh, M; Britton, K; Baker, P; Stillman, T; Martin, SR; Rice, D; Engel, P (1994)
A putative catalytic aspartyl residue, Asp-165, in the active site of clostridial glutamate dehydrogenase has been replaced with serine by site-directed mutagenesis. The mutant enzyme is efficiently overexpressed in Escherichia coli as a soluble protein and can be successfully purified by the dye-ligand chromatographic procedure normally employed for the wild-type enzyme. By several criteria, including circular dichroism spectrum, sulphydryl reactivity with Ellman's reagent, crystallization and mobility in non-denaturing electrophoresis, the enzyme appears to be correctly folded. NAD+ protects the D165S mutant against modification by Ellman's reagent, suggesting unimpaired binding of coenzyme. In standard assays the specific activity is decreased 10(3)-fold in the reductive amination reaction and 10(5)-fold for oxidative deamination. Kinetic studies show that apparent Km values for NADH and 2-oxoglutarate are almost unchanged. The large reduction in the reaction rate coincides with a weakening of the affinity for ammonium ion (Km > 300 mM, compared with 60 mM for the wild-type). The data are entirely consistent with the direct involvement of D165 in catalysis rather than in the binding of coenzyme or 2-oxoglutarate.